ELECTROCHEMICAL BEHAVIOR OF AgCu50 IN ALKALINE MEDIA IN THE PRESENCE OF CHLORIDES AND 2-MERCAPTOBENZOTHIAZOLE - Vesna Grekulovic; Mirjana Rajcic Vujasinovic; Aleksandra Mitovski; Ljubisa Balanovic (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
Abstract Electrochemical behavior of an alloy AgCu50, pure copper, and pure silver, respectively, was investigated by measuring the open circuit potentials using anodic potentiodynamic polarization and potentiostatic method in 0.1 moldm-3 NaOH + 0.02 moldm-3 NaCl solution, without and with adding 2-mercaptobenzothiazole in various concentrations (0.00001 – 0.001 moldm-3). Anodic polarization curves for AgCu50 alloy, showed four current peaks. Potentiostatic curves showed that values of the stationary current densities drop down with the increase of 2-mercaptobenzothiazole concentration in the electrolyte. The electrode surface was analyzed by optical microscopy after the potentiostatic oxidation. Micrographs confirmed that 2-mercaptobenzothiazole has got the inhibitory effect by forming the film of CuMBT and AgMBT which protect the electrode surface from corrosion. Keywords: silver, copper, alloy AgCu50, potentiodynamic polarization, 2-mercaptobenzothiazole